Navigating the linguistic gap: Exploring translanguaging through the eyes of Indonesian mechanical engineering students - Retnowaty, Retnowaty (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This paper examines the gap between theoretical support for translanguaging in multilingual education and limited understanding of student perspectives, particularly in English for Specific Purposes (ESP) contexts in Indonesia. Indonesian engineering students’ perceptions of translanguaging practices in ESP courses was investigated, hypothesizing that students would view translanguaging positively while recognizing contextual appropriateness concerns. Data was collected from 61 Indonesian engineering students through an online questionnaire and analyzed to understand perceptions of translanguaging in academic contexts. Results indicated most students supported translanguaging as an intuitive strategy that increases confidence, motivation, and comprehension of technical concepts, with high mean scores affirming its value for inclusivity and overcoming language barriers in complex engineering subjects. Students reported translanguaging enhanced engagement through facilitating group work, peer support, and discussions, though some participants associated it with English deficiency. Findings suggest strategic implementation of translanguaging can address language barriers and enhance engineering education while preparing students for global professional environments. However, instructors should be mindful of some students' concerns about appropriate contexts for translanguaging use, particularly regarding casual situations and classroom expectations.